Ukuran Perusahan Sebagai Variabel Kontrol Dalam Determinan Struktur Modal Manufaktur - I Wayan Wardita; Ni Made Gunastri; I Made Purba Astakoni; Ida Bagus Swaputra (Universitas Warmadewa, 2021)
This study raises several objectives, namely (1) analyzing the effect of profitability on capital structure, (2) analyzing the effect of asset structure on capital structure, (3) analyzing the effect of business risk on capital structure, (4) comparing the results of the overall analysis with both control and variable variables. without the firm size control variable. The population in this study were all manufacturing companies in the cosmetics and household goods sector listed on the Indonesia Stock Exchange for the 2016-2020 period, namely seven companies. The samples in this study were taken according to predetermined criteria. Based on the provisions that have been set, a sample of five companies was selected. The data analysis technique in this study uses a regression approach where the processing uses the help of the Eviews Version 12 program, considering that the data analyzed is in the form of panel data. Based on the model test, both through the determination test and statistical F test, very good results were obtained. The first hypothesis which states that profitability has a significant negative effect on capital structure has not been accepted (rejected). The second hypothesis which states that business risk has a significant negative effect on capital structure has not been accepted (rejected). The third hypothesis which states that asset structure has a significant positive effect on capital structure is acceptable. The results of the comparison involving the control variable of firm size, it can be explained that the model is better without the control variable because the results are suppressing or weakening the adopted model.